Entomologic and molecular investigation into Plasmodium vivax transmission in Singapore, 2009 - Lee-Ching, N.; Kim-Sung, L.; Cheong-Huat, T.; Peng-Lim, O.; Sai-Gek, L.P.; Raymond, L.; Yee-Ling, L.; Suhana, S.; Pei-Pei, C.; Kit-Yin, W.; Vythilingam, Indra (2010)
Background Singapore has been certified malaria free since November 1982 by the World Health Organization and despite occasional local transmission, the country has maintained the standing. In 2009, three clusters of malaria cases were reported in Singapore. Methods Epidemiological, entomological and molecular studies were carried out to investigate the three clusters, namely Mandai-Sungei Kadut, Jurong Island and Sembawang. Results A total of 29 malaria patients, with no recent travel history, were reported in the three clusters. Molecular analysis based on the msp3Î± and msp1 genes showed two independent local transmissions: one in Mandai-Sungei Kadut and another in Sembawang. Almost all cases within each cluster were epidemiologically linked. In Jurong Island cluster, epidemiological link remains uncertain, as almost all cases had a unique genetic profile. Only two cases shared a common profile and were found to be linked to the Mandai-Sungei Kadut cluster. Entomological investigation found Anopheles sinensis to be the predominant Anopheline in the two areas where local transmission of P. vivax was confirmed. Anopheles sinensis was found to be attracted to human bait and bites as early as 19:45 hrs. However, all Anopheles mosquitoes caught were negative for sporozoites and oocysts by dissection. Conclusion Investigation of P. vivax cases from the three cluster areas confirmed the occurrence of local transmission in two areas. Although An. sinensis was the predominant Anopheline found in areas with confirmed transmission, the vector/s responsible for the outbreaks still remains cryptic.